2019
DOI: 10.1038/s41598-019-44054-0
|View full text |Cite
|
Sign up to set email alerts
|

Interface-inspired formulation and molecular-level perspectives on heat conduction and energy storage of nanofluids

Abstract: Aiming for the introduction of stability requirements in nanofluids processing, an interface-based three-step method is proposed in this work. It is theory-based design framework for nanofluids that aims for a minimum tension at the solid-liquid interface by adjusting the polar and dispersive components of the base fluid to meet those of disperse nanomaterial. The method was successfully tested in the preparation of aqueous nanofluids containing single-walled carbon nanotubes that resulted to be stable and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 69 publications
(65 reference statements)
0
13
0
Order By: Relevance
“…Density was underestimated from the experimental values 27 30 by between 0.8% (propylene glycol) and 4.6% (propanol). While 10 Å is not unprecedented 31 , a 12 Å cutoff is perhaps more common for studies of this nature 15 , 16 , 20 , 32 , however in tests under the conditions used in this study with ethylene glycol we found the difference in density, thermal conductivity and its components to be negligible under these two cutoff distances. Length of bonds involving one hydrogen bond, and angles involving two hydrogen bonds were fixed using the SHAKE algorithm 33 .…”
Section: Simulation Detailsmentioning
confidence: 57%
“…Density was underestimated from the experimental values 27 30 by between 0.8% (propylene glycol) and 4.6% (propanol). While 10 Å is not unprecedented 31 , a 12 Å cutoff is perhaps more common for studies of this nature 15 , 16 , 20 , 32 , however in tests under the conditions used in this study with ethylene glycol we found the difference in density, thermal conductivity and its components to be negligible under these two cutoff distances. Length of bonds involving one hydrogen bond, and angles involving two hydrogen bonds were fixed using the SHAKE algorithm 33 .…”
Section: Simulation Detailsmentioning
confidence: 57%
“…Such adjustment leads to a minimum tension at the solid–liquid interface by using the non-ionic surfactant Triton X-100 (Panreac Quimica SLU, Barcelona, Spain). This approach showed better stability and an anomalous enhancement in thermo-physical properties based on the molecular dynamic simulation, even at 70 °C [ 40 ]. Meanwhile, in another recent report, Li et al have shown the spacer length optimization of cationic Gemini surfactant that improved the colloidal stability of aqua-based Au and Ag nanofluids, along with the pH dependency of stability.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, a molecular dynamic simulation investigation of the Triton X-100 surfactant has also shown ~79.5% enhancement in thermal conductivity for aqua-based carbon nanotube nanofluids at 70 °C. This enhancement was attributed to the better colloidal stability with the inclusion of a surfactant which lowers the interfacial tension between the solid–liquid network [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…While most studies of energy harvesters typically consider uncorrelated environmental noise, the reality is that this limit is an idealisation to describe noises correlated over very short times. However, in many potential applications, like electromagnetic plasmas 30 , non-Newtonian fluids 31 or nanofluidics 32 , the noise fluctuations may exhibit long correlation times. Therefore, energy harvesters that can take advantage of the low end frequency band without the need of fine tuning the device response frequency to the right bandwidth, are most welcome.…”
Section: Discussionmentioning
confidence: 99%